The Meaning of Hawa in the Qur’an: A Semantic Analysis of the Perspective Toshihiko Izutsu - Ahmad Mudakir; Dadang Darmawan; Wildan Taufiq (Jurnal Iman dan Spiritualitas, 2022)
Research on hawa is essential to do, because in the Qur’an there is a correlation between hawa and injustice, misguidance, and other negative things related to aqidah, worship, law, and social interaction. In addition, in the Qur’an there is the meaning of hawa which has a positive connotation. It is interesting to study using Toshihiko Izutsu's semantic analysis to get the meaning network and the maudu'i to get the concept. This analytical model is called the combinatorial model. Qualitative research is the approach used. The source of the data comes from the library. The research method used is descriptive analysis research.